Who gains from nominal devaluation? An empirical assessment of Euro-area exports and imports - Sebastian Breuer; Jens Klose (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2013)
In early 2013 rumors about the Euro-appreciation gained momentum, which may lead to decreases in exports and increases in imports of the member states. Therefore, we investigate the impact of changes in the nominal Euro exchange rate vis-à-vis major currencies on export and import performance of nine different Euro-area-countries. To disentangle the true equilibrium elasticities SURE system error correction models (SSECM) are estimated for nominal exchange rate changes versus the rest of the world or other major currencies. To differentiate between price level changes and changes of the nominal exchange rate, a country's export and import equation is estimated using separately the nominal rate and the relative price/ unit labor cost as regressors. Results of Wald-tests indicate that assuming both variables to have the same influence on exports and imports is misleading. Whether the relative price/ unit labor costs elasticities are high or low depends crucially on which indicator is chosen, while the effect of nominal exchange rate changes can be estimated robustly for all countries in the sample. Especially France and Spain are hit by a Euro appreciation since their exports are highly exchange rate elastic. However, for France, this effect is at least partly offset by an also negative exchange rate elasticity of imports.
Keywords: 330